The retirement boom : an all inclusive guide to money, life, and health in your next chapter - Allen, Catherine (Writer on retirement) (Career Press, 2016)
Baby Boomers are reinventing retirement just as they have so many other aspects of their lives. They will live longer and be healthier than their parents and grandparents, and they plan to remain relevant, be fulfilled, and leave legacies. Many will continue to work well into their 70s and 80s, some because they want to, others because they need to.